Effect of high fat diet feeding on resistance to bacteria infection in D. melanogaster - Mirosavljević, Vanja (Jihočeská univerzita, 2019)
In order to obtain further knowledge in effects of high fat diet on resistance to bacterial infection, the following aims will be discussed: - Identification of effects of HFD feeding on resistance to bacterial infection - Describing the effect of HFD feeding on ability to fight the bacteria - Comparison of the effect of HFD feeding on level of free metabolites (glucose, glycogen and lipids) - Analysis of triglyceride amounts in the whole body of Drosophila and hemocytes particularly
Effect of high fat diet feeding on resistance to bacteria infection in D. melanogaster